The Young Generation of Catholics in the Face of Ecological Problems Exemplified by the Initiatives of the Catholic Youth Association - Andrzej Lubowicki (Studia Ecologiae et Bioethicae)
The Catholic Youth Association (Pol. KSM) operates within 41 dioceses of the Roman Catholic Church in Poland and, according to data from 2019, has approx. 20,000 members in almost 1,000 parish units and community circles. Numerous initiatives undertaken by KSM include, among others, activities aimed at protecting creation. This study presents several of the most important ecological projects implemented by KSM: 1. Bug, the River of Life - Education for Youth, Youth for Sustainable Development; 2. Youth of this Earth; 3. Electro Responsible; 4. Kayaking Patrol of St. Francis; 5. Youth for the Environment; 6. Youth Environment.